1992
DOI: 10.1017/s0021900200043825
|View full text |Cite
|
Sign up to set email alerts
|

Optimality of index policies for stochastic scheduling with switching penalties

Abstract: We investigate the impact of switching penalties on the nature of optimal scheduling policies for systems of parallel queues without arrivals. We study two types of switching penalties incurred when switching between queues: lump sum costs and time delays. Under the assumption that the service periods of jobs in a given queue possess the same distribution, we derive an index rule that defines an optimal policy. For switching penalties that depend on the particular nodes involved in a switch, we show that altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Priority-based scheduling has been studied in the context of queueing theory [49,[81][82][83][84][85][86][87]. It has been stated, that "there are no undiscovered priority index sequencing rules for minimizing total delay costs" [82].…”
Section: Optimization Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Priority-based scheduling has been studied in the context of queueing theory [49,[81][82][83][84][85][86][87]. It has been stated, that "there are no undiscovered priority index sequencing rules for minimizing total delay costs" [82].…”
Section: Optimization Strategymentioning
confidence: 99%
“…However, the considered prioritization strategies were restricted to functions of the current queue length, i.e. to the number of vehicles that have already been stopped [81,88]. In contrast, our anticipation model (see Sec.…”
Section: Optimization Strategymentioning
confidence: 99%
“…Switching jobs from one machine to another incurs a variety of setup costs (Duenyas and Van Oyen (1996), Karaesmen and Gupta (1997), Reiman and Wein (1998), ) and switching costs (Van Oyen and Teneketzis (1993), Koole (1997), Van Oyen et al (1992), Kolonko and Benzing (1985)). Unfortunately, Bank and Sundaram (1994) showed that in the presence of switching costs it is not possible to define an index for each arm such that the resulting strategy produces the maximized payoffs.…”
Section: Switching Costsmentioning
confidence: 99%
“…The objective is to minimize the expected costs of serving all the jobs. The special case where there is only one job in a family is completely characterized by Santos and Magazine (1985) in a deterministic model, and Van Oyen et al (1992) in a stochastic model. Let x n denote the number of identical jobs in family n. The index for family n is equal to…”
Section: Van Oyen and Pichitlamken (1999)mentioning
confidence: 99%
“…They partially characterized the optimal policy and developed some dynamic heuristics. Van Oyen et al [27] treated versions without arrivals but with heterogeneous service processes and either set-up costs or set-up times. They proved that an index policy is optimal and computed the optimal indices for cases with lump-sum set-up costs and those with set-up times.…”
Section: Introductionmentioning
confidence: 99%